Active Supervision: Preventing Behavioral Problems Before They Occur. (April 2019) - Haydon, Todd; Hunter, William; Scott, Terrance M.
The current body of research on classroom environments identifies key proactive instructional strategies that when implemented effectively can reduce the likelihood of problematic behavioral incidents by students. One strategy known as active supervision has demonstrated positive outcomes across school settings, including classrooms, hallways, cafeterias, and playgrounds. In this article, authors provide a definition of active supervision, empirical support for its use, a detailed description of how to implement it, and resources for further study.